ACOTANDO ESPACIOS. CONTROL ESTATAL EN GUANACASTE 1860-1940: CONSTRUYENDO EL PODER EN GUANACASTE. - Marín Hernández, Juan José (2008)
The article examines the current configuration of the Province of Guanacaste in terms of its historical construction, which far from being born as an autonomous body, connate and natural, it developed first into a territorial unit to later become a region. Within the same province one can find subregions, each one displaying its local and identity particularities, which have in turn allowed for the acknowledgment of other more general identities, such as that of the Guanacaste native inhabitant and the ‘Tico’, common name used for Costa Rican. The article presents a first-time evaluation on the insertion process of Guanacaste into the national context and how, as of this space obtained, other hegemonic processes were brought about. These objectives are viewed in the light of two specific problem areas: the economic and cultural areas.